C,N,0 ABUNDANCES IN THE ATMOSPHERES OF FOUR LATE GIANT STARS - Shavrina, A. V.; Yakovina, L. A.; Boyarchuk, M. E.; Bikmaev, I. F. (Одеські астрономічні публікації, 2017)
The abundance of C,N,0 have been determined for 4 late giant stars from atomic and molecular spectra by the method of synthetic spectrum.